Cervical pessary for preventing preterm birth in twin pregnancies with short cervical length: a systematic review and meta-analysis. (17th December 2017) - Saccone, Gabriele; Ciardulli, Andrea; Xodo, Serena; Dugoff, Lorraine; Ludmir, Jack; D'Antonio, Francesco; Boito, Simona; Olearo, Elena; Votino, Carmela; Maruotti, Giuseppe Maria; Rizzo, Giuseppe; Martinelli, Pasquale; et al.
Abstract: Objective: To evaluate the effectiveness of cervical pessary for preventing spontaneous preterm birth (SPTB) in twin pregnancies with an asymptomatic transvaginal ultrasound cervical length (TVU CL) in the second trimester. Methods: We performed a meta-analysis including all randomized clinical trials (RCTs) comparing the use of cervical pessary (i.e. intervention group) with expectant management (i.e. control group). The primary outcome was incidence of SPTB <34 weeks. Results: Three trials, including 481 twin pregnancies with short cervix, were analyzed. Two RCTs defined short cervix as TVU CL ≤25 mm and one as TVU CL ≤38 mm. Pessary was not associated with prevention of SPTB, and the mean gestational age at delivery and the mean latency were similar in the pessary group compared to the control group. Moreover, no benefits were noticed in neonatal outcomes. Conclusions: Use of the Arabin pessary in twin pregnancies with short TVU CL at 16–24 weeks does not prevent SPTB or improve perinatal outcome.